An 8nA-512μA Current-to-Digital Converter With Mixed-Signal Coarse-Fine Subrange Normalization - Kim, Se Young; Jee, Dong Woo (IEEE Transactions on Circuits and Systems II: Express Briefs, 2023)
This brief presents a current to digital convertor (CDC) with low power, wide dynamic range and fast conversion speed. Proposed coarse converter extends the maximum input current range, and achieves fast conversion speed with the input adaptive control scheme. Capacitive transimpedance amplifier (CTIA) based fine converter digitizes the residue current and achieves fine resolution. Proposed mixed-signal coarse-fine subrange normalization technique enables seamless processing of the final converter output. The proposed CDC implemented in 0.18μm CMOS process converts input current up to 512μA with 7.8125nA resolution and 400μs conversion time. Power consumption is 79.4 μW.
Keywords: current; Capacitive trans-impedance amplifier; Coarse-fine architecture; Code; Current sensors; Current-to-digital converter; Digital converters; Frequency measurements; Normalisation; Power; Power measurement; Subrange; Subrange normalization; Trans impedances; Voltage-controlled-oscillator; capacitive trans-impedance amplifier; coarse-fine architecture; Current sensor; current-to-digital converter; subrange normalization